Incidence of adverse perinatal outcomes in highly vulnerable pregnant women – the Mothers of Rotterdam study - Kajal S. C. Mohabier; Hanneke P. de Graaf; Eric A. P. Steegers; Loes C. M. Bertens (BMC Pregnancy and Childbirth)
Abstract Background Socioeconomic disadvantaged circumstances are known to affect health outcomes, but during pregnancy it also affects the growth and development of the fetus. This often results in adverse perinatal outcomes and other long lasting effects. Here we refer to pregnant women living in such circumstances as a highly vulnerable population. Objectives To study adverse perinatal outcomes in highly vulnerable pregnant women within the Mothers of Rotterdam (MoR) study and to compare findings to the outcomes of women in the Netherlands as a whole and the city of Rotterdam. Methods Pregnancy and childbirth data from women participating in the MoR study (2015–2019) was requested from their obstetric professional. For comparison, data from the Dutch national birth registry (Perined) were used representing women in the Netherlands and Rotterdam. Main outcome measures were preterm birth (PTB) and small for gestational age (SGA). Secondary outcome measures were perinatal mortality and a low Apgar score. Only singleton viable pregnancies (i.e. birthweight above 500 g or born after 22 + 0 weeks of gestation) were included in this study. Prevalence rates and corresponding 95% confidence intervals (95%CI) were calculated for all outcomes in each group. Direct standardization was used to account for possible differences in case-mix composition between the studied groups. Results Data on 346 childbirths within the MoR study were retrieved and compared to 813,755 and 34,009 childbirths in the Netherlands and Rotterdam, respectively. The prevalence of PTB (4.34% (95%CI 2.19–6.48) was lower in the MoR population compared to both the Netherlands (6.21% (95%CI 6.16–6.27)) and Rotterdam (6.39% (95%CI 6.13–6.65)). The prevalence of SGA (21.09% (95% CI 16.80–25.40)) was higher in the MoR population compared to both the Netherlands (10.11% (95%CI 10.04–10.17)) and Rotterdam (13.28% (95%CI 12.92–13.65)). There were no cases of perinatal mortality registered in the MoR population. The prevalence of a low Apgar score (0.87% (95%CI 0.00–1.84)) was lower in the MoR population. Conclusions Our study found unexpected low PTB and high SGA prevalence rates in the MoR population compared to the Netherlands and Rotterdam. Mechanisms through which socioeconomic disadvantaged circumstances affect perinatal health seem to work differently in various strata of vulnerable populations.